GCT-29. DOES TUMOUR MARKER DECLINE PREDICT OUTCOME IN INTRACRANIAL NON-GERMINOMATOUS GERM CELL TUMOURS (NGGCTs)?. (4th December 2020) - Conter, Cecile Faure; Lardy-Cleaud, Audrey; Murray, Matthew; Nicholson, James; Guerrini-Rousseau, Lea; Palenzuela, Gilles; Alapetite, Claire; Garre, Maria Louise; Kortmann, Rolf; Saran, Frank; Ajithkumar, Thankamma; Pietsch, Torsten; et al.
Abstract: INTRODUCTION: The prognostic impact of tumour marker (TM) decline rate has been demonstrated for extracranial poor prognostic non-seminomatous/germinomatous germ cell tumours (NGGCT). The current series aimed to assess if this finding can be applied to intracranial primaries. METHODS: Patients were retrieved from the SIOP-CNS-GCT-96 database. They were selected if they had i/assessable values of serum alpha-fetoprotein (AFP) and/or human chorionic gonadotropin (HCG) before and 18 to 28 days after the first course of chemotherapy and ii/ available data for outcome. Decline rate was calculated using a logarithmic transformation and expressed as time to normalization (TTN) as published by Fizazi (JCO 2004). TTN≤ 9 weeks for AFP and ≤ 6 weeks for HCG were considered as favourable decline rate. Prognostic impact of TTN on outcomes was assessed using the log-rank test. RESULTS: Out of 149 patients with NGGCT, 59 were evaluable for both HCG and AFP TTN of whom 44 (74%) had a favourable decline rate. After a median follow-up of 88 months (2–251), 20 relapses and 15 deaths occurred. The 5-year PFS rates were 72% and 60% in patients who had a favourable and an unfavourable TTN, respectively (p=0.15). The 5-year OS rates were 77 % and 69%, respectively (p=0.66). Separate analysis of TTN based only on AFP or only on HCG gave similar results. CONCLUSION: Despite the use of a methodology similar to that used in extracranial NGGCT, no significant impact of serum TM decline on prognosis was observed, but insufficient statistical power cannot be ruled out.